PENGGUNAAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN HASIL BELAJAR MATERI SISTEM PENCERNAAN SISWA SEKOLAH DASAR - Karyati; Zamsolih, Inti; Suciana, Dola (Prosiding Temu Ilmiah Nasional Guru, 2023)
Patterns of interaction between teachers and students are strongly influenced by developments in the digital world in education. When traditional education is practiced, most students who have a good level of ability to use technology tend to become disinterested. The purpose of this research is to describe the use of audio-visual media to improve learning outcomes. Classroom action research is used as a descriptive research method. The method used to collect data in this study is a test technique that is carried out once in each cycle. The instrument used is a description test to find out how far students' understanding and ability to receive and absorb learning material. The data obtained were then analyzed using a percentage descriptive analysis method. This technique is used to measure the increase in student learning outcomes after the use of audiovisual media is applied. Based on the results of the study, during the pre-cycle the average student score was only 60 with classical completeness of 38.46%. In cycle 1 the average value of students rose to 64 with classical completeness of 46.15%. Then in cycle 2 the average value of students experienced a significant increase, namely 69 with 69.23% classical completeness. In the final cycle, namely cycle 3, the increase in student learning outcomes was seen to increase significantly with the class 77 average with classical completeness reaching 92.31%. Based on this description, researchers can draw conclusions that the use of audiovisual media has a significant impact on improving student learning outcomes.